Investigating social orienting in children with Phelan-McDermid syndrome and ‘idiopathic’ autism - Antonia San José Cáceres; Emma Wilkinson; Jennifer Cooke; Victoria Baskett; Charlotte Blackmore; Daisy Victoria Crawley; Allison Durkin; Danielle Halpern; María Núñez; Page Siper; Declan G. Murphy; Jennifer Foss-Feig; et al. (Journal of Neurodevelopmental Disorders, 2024)
Abstract Background Phelan-McDermid syndrome (PMS) is a rare genetic syndrome characterized by developmental delay/intellectual disability, absent or delayed speech, physical dysmorphic features and high rates of autistic features. However, it is currently unknown whether people with PMS have similar neurocognitive atypicalities to those previously identified in idiopathic autism. Disruption in social orienting has previously been suggested as an early hallmark feature of idiopathic autism that impacts social learning and social interaction. Methods This study used a semi-naturalistic task to explore orienting to social versus non-social stimuli and its relation to clinical features in individuals diagnosed with PMS, autism, and neurotypical children recruited in the United States and the United Kingdom. Results At the group level, autistic and neurotypical children responded on average more often to social than non-social stimuli, while children with PMS responded similarly to both stimulus types. Both clinical groups responded significantly less often to social stimuli than neurotypical children. In addition, we found considerable variability in orienting responses within each group that were of clinical relevance. In the autism group, non-social orienting was associated with mental age, while in the PMS group social and non-social orienting were related to strength of autistic features. Conclusions These findings do not support specific social motivation difficulties in either clinical group. Instead, they highlight the importance of exploring individual differences in orienting responses in Phelan-McDermid Syndrome in relation to autistic features. Trial registration NA.